Correction to: Fuzzy forward dynamics of distinct gait phases with a prosthetic foot (Computational Mechanics, (2022), 10.1007/s00466-022-02167-w) - Scheiterer, Eduard; Leyendecker, Sigrid (Computational Mechanics, 2022)
A Correction to this paper has been published: 10.1007/s00466-022-02167-w.
CRIS-Team Scopus Importer:2022-08-19